THE EFFECT OF BIO URINE APPLICATION FREQUENCIES ON THE GROWTH AND YIELDS OF ONION PLANTS (Allium fistulosum L.) ON ALUVIAL LAND - Erma Sulistia Nengsih; Rahmidiyani Rahmidiyani; Wasi'an Syafiuddin (Jurnal Sains Pertanian Equator, 2019)
Erma Sulistia Nengsih1),Rahmidiyani2),Wasi’an2)1) Faculty of Agriculture Students, Tanjungpura University2) Teaching Staff of the Faculty of Agriculture, Tanjungpura University, Pontianak e-mail : sulistianingsiherma123@gmail.com                                                         ABSTRACT                         This study aims to determine the best frequency of bio-urine appalication on the growth and yield of onion plants on alluvial soil. This research was carried out in the experimental garden of the Faculty of Agriculture, Tanjungpura University Pontianak, from April 6th, 2018 to May, 25th 2018. The research method used was a Completely Randomized Design (CRD) consisting of 5 treatments, namely (f1): without bio urine, (f2): appalied once in a time (14 HST), 100 ml / L water, (f3): twice application (14.24 HST), 50 ml / L water, (f4): three times application (14,24,34 HST), 33 , 33 ml / L of water, and (f5): four times of application (14,24,34,44 HST), 25 ml / L of water. Each treatment were repeated 5 times, and each experimental unit consisted of 3 plant samples, so that the total number of plants were 75 plants. Observation variables in this study were plant height (cm), root volume (cm3), number of tillers per clump (fruit), plant fresh weight per clump (g), and plant dry weight per clump (g). The results of this study indicated that the effect of the frequency of 100 ml bio-urine giving the same response to the plant height, root volume, number of tillers, fresh weight and dry weight of onion leaves. Keywords : alluvial bio urine, onion,